2021
DOI: 10.3390/su13031377
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting Waste Thermal Energy Using a Surface-Modified Carbon Fiber-Based Thermo-Electrochemical Cell

Abstract: An important direction in the development of energy saving policy is harvesting and conversion into electricity of low-grade waste heat. The present paper is devoted to the improvement of the efficiency of thermo-electrochemical cells based on carbon fiber electrodes and potassium ferri-/ferrocyanide redox electrolyte. The influence of the carbon fiber electrode surface modification (magnetron deposition of silver and titanium or infiltration implantation of nanoscale titanium oxide) on the output power and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
(32 reference statements)
0
11
0
Order By: Relevance
“…These include activated carbon textiles, 39,40 free-standing carbon-based materials, 41,42 multiwall carbon nanotube foams, 43 nickel hollow microspheres, 44 and surface-modified carbon fibers. 45 The large electroactive surface area of porous electrodes enables rapid diffusion of the electrolyte and results in an increase in exchange current density between the electrode and the electrolyte. Therefore, to further improve the thermoelectric performance of thermocells, optimization of electrode materials would be helpful.…”
Section: àmentioning
confidence: 99%
“…These include activated carbon textiles, 39,40 free-standing carbon-based materials, 41,42 multiwall carbon nanotube foams, 43 nickel hollow microspheres, 44 and surface-modified carbon fibers. 45 The large electroactive surface area of porous electrodes enables rapid diffusion of the electrolyte and results in an increase in exchange current density between the electrode and the electrolyte. Therefore, to further improve the thermoelectric performance of thermocells, optimization of electrode materials would be helpful.…”
Section: àmentioning
confidence: 99%
“…Besides already known chalcogenides properties of the p- and n-type conducting thermoelectric materials may be improved with various metallic [ 6 ], metal oxide [ 7 ] as well as carbon based materials like graphene [ 8 ], carbon fibers [ 9 ] and carbon nanotubes (CNTs) [ 10 , 11 ]. In CNT based polymer-CNT composite materials the CNTs within the polymer matrix form electrically but not thermally conductive networks, thus improving thermoelectrical ZT of the composite, as well as their thermal stability and mechanical properties [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…They may become the primary materials for liquid and gas adsorption and environmental protection. Therefore, Denis et al investigated the modification of carbon fiber electrode surfaces using magnetron sputtering by depositing silver and titanium or infiltration injection of titanium oxide nanoparticles to improve the electrodes and its effect on the output power and impedance equivalent scheme parameters of thermoelectric cells [ 113 ], as shown in Figure 7 a–f. It was found that the nature of the electrode surface modification can increase the internal resistance of the cell by three orders of magnitude.…”
Section: Improving the Efficiency Of Single Thermocellmentioning
confidence: 99%
“…Plots of maximum power density versus temperature difference between the hot and cold sides of the cell ( e ) for cells with a salt bridge and ( f ) for cells in the coin cell CR2025. (Reproduced with permission from [ 113 ]. Copyright 2021 MDPI).…”
Section: Figurementioning
confidence: 99%